The impact of physical exercise on mobile phone addiction among college students: a study based on Chinese universities - Bo Shi; Di Wang; Mengfan Liu (Frontiers in Psychology)
To explore the impact of physical exercise on mobile phone addiction (MPA) among college students and the underlying psychological mechanisms, a questionnaire survey method is utilized to conduct empirical analysis on students from multiple colleges in China. This study uses Physical Activity Rating Scale-3, Mobile Phone Addiction Tendencies Scale (MPATS), Self-Acceptance Questionnaire, and Chinese Perceived Stress Scale to measure psychological variables such as physical activity level, degree of MPA, and self-acceptance and perceived stress among college students. The study reveals the mechanism of physical exercise in reducing MPA. The research results demonstrate a significant negative correlation between MPA and physical exercise. Exercise frequency has the most remarkable influence on withdrawal symptoms and salience behaviors, with correlation coefficients of −0.35 and −0.30, respectively. These findings show that regular engagement in physical activity can substantially mitigate the dependency of college students on mobile phones. Exercise intensity and exercise duration also have a negative effect on MPA, and the correlation coefficient of exercise intensity on withdrawal symptoms is −0.32. Furthermore, self-acceptance as a moderating variable plays an important protective role within the nexus between physical exercise and MPA. Students with higher self-acceptance levels show significant remission in both withdrawal symptoms (β = −0.30) and mood changes (β = −0.28), with model interpretability increasing from 0.34 to 0.43. On the contrary, perceived stress, as a risk-regulating variable, is positively correlated with MPA, and the impact of perceived stress on withdrawal symptoms is 0.35. Additionally, under conditions of elevated perceived stress, the physical exercise’s mitigating effect on mobile phone dependence is attenuated. Therefore, self-acceptance can enhance the individual’s self-identity, weaken the negative emotional reaction brought by MPA, and help to improve the intervention effect of physical exercise. On the contrary, perceived stress weakens the relieving effect of physical exercise on mobile phone dependence, and individuals with high-stress levels are more likely to maintain MPA behavior. This study makes a valuable contribution to the literature on the interplay.